A book-like organic based electrode with high areal capacity for high performance flexible lithium/sodium-ion batteries. Issue 73 (24th August 2022) - Huang, Tao; Gao, Hong; Chen, Jun; Liu, Hao; Wu, Dongqing; Wang, Guoxiu
Abstract : A free-standing multilayer book-like organic based electrode was prepared, presenting high conductivity and excellent flexibility, thereby achieving outstanding performance for flexible lithium-ion batteries and sodium-ion batteries. Abstract : By directly bonding the monolayer organic based electrodes together to assemble the book-like multilayer electrode, increased areal capacity and high flexibility can be achieved. The electrodes represent 5.88 mA h cm −2 at 0.7C and 5.24 mA h cm −2 at 0.2C areal capacity in lithium-ion and sodium-ion batteries, respectively.